Pembangunan Strategi Pemasaran untuk Meningkatkan Daya Saing Rumah Sakit di Era Digital - Purwadhi; Yani Restiani Widjaja; Khusha Ibliyah; Sri Rahmawati Pontoh (MES Bogor, 2024)
Increased competition in the healthcare industry, especially in the digital era, requires hospitals to develop effective marketing strategies. This research aims to develop an appropriate marketing strategy to improve hospital competitiveness in the digital era. The research method used is descriptive qualitative with a literature study approach and SWOT analysis. Data were obtained from various sources, such as scientific journals, books, and articles related to hospital marketing in the digital era. The results showed that effective marketing strategies for hospitals in the digital era include building brand awareness through digital platforms, increasing engagement with patients through social media and websites, utilizing digital technology to improve patient services, building networks and collaborations with related parties, and building effective referral systems. This marketing strategy is expected to increase the hospital's competitiveness, attract more patients, and increase patient satisfaction.